The chemistry of heterocycles in the 21st century; Russian Chemical Reviews; Vol. 93, iss. 7 - Charushin V. N. Valery; Verbitskiy E. V.; Chupakhin O. N.; Mironova I. A. Irina Andreevna; Postnikov P. S. Pavel Sergeevich; Zhdankin V. V. Viktor Vladimirovich; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich) (2024, 2024)
Title screen